Neoadjuvant chemotherapy in patients with stages III/IV breast cancer disease surgical experience at Muhimbili National Hospital, Dar es Salaam, Tanzania (Tanzania Medical Journal, 2015)
Background: Breast cancer disease is a health problem of public importance worldwide. In developing countries where majority of patients present late with locally advanced disease: further creates management difficulties to surgeons, oncologists and other medical personnel as to what management protocol suits a particular patient. The aim of this study was to determine disease response, recurrence and development of distant metastasis with the use of chemotherapy in the form of neoadjuvant chemotherapy.Patients and methods: This was a prospective study that had enrolled a total of 57 patients with locally advanced breast cancer disease between January 2003 and December 2005. After completion of treatment patients were followed at 6months interval for 2 years. Patients who fulfilled inclusion criteria at their initial presentation had baseline data including patient’s demography, size of the tumor, node status, presence of distant metastasis and finally stage of the tumor were established. 43 patients of the study group were given chemotherapy in the form of neoadjuvant chemotherapy at 3 weeks interval based on haematological stability until they had completed 4 cycles of dosages before they underwent surgical operation. They were given cyclophosphamide and adriamycin (CA-regime). During subsequent visits of chemotherapy; reassessment was done and recorded. After surgery patient were followed at 6 months interval to assess presence of local recurrence, distant metastasis or death. 14 patients of the study group had surgical treatment before they were given chemotherapy and these formed the adjuvant chemotherapy group. In this group chemotherapy was also given at 3 weeks intervals based on haematological stability and after completion were followed at 6 months interval to determine presence of local recurrence, distant metastasis or death. Radiotherapy was given to any patient in either group where suspicion of residual tumor was present. Patients’ data were entered in an SPSS window 11.5 program and data were analyzed.Results: Patient had mean age of 44.14±8.42 years, with age ranging from 29 to 65 years. 81.5% of patients were 50 years and below and were premenopausal. The mean duration of symptoms at presentation was 3.3±1.3 months with minimum and maximum of 1 and 7 months respectively. 19.3% of the study patients had family history of breast cancer disease to their first degree relatives. Ductal carcinoma was the commonest histopathological finding in 82.5% of all cases. Neoadjuvant chemotherapy was found to be effective in down staging locally advanced breast cancer disease and the response rate was 50-83.3%. During follow up period local recurrence occurred more on the 12 and 18 months in the adjuvant chemotherapy group as compared to the neoadjuvant chemotherapy group and this difference was statistically significant (?<0.05). A relatively higher incidence of distant metastasis was also noted on the 24 month of follow up in the adjuvant chemotherapy group as compared to the neoadjuvant chemotherapy group and the difference was statistically significant (?<0.05). No statistical difference was noted with regards to death in either of the treatment groups.Conclusion: This study has shown that neoadjuvant chemotherapy is associated with high response rate in down staging of locally advanced breast cancer and hence improving patient management from palliative to more definitive surgical management. It has further shown that use of neoadjuvant chemotherapy is associated with low recurrence and late emergence of distant metastasis when compared to patients who undergoes first surgery and then chemotherapy in a form of adjuvant chemotherapy. We therefore highly recommend the use of neoadjuvant chemotherapy in patients with locally advanced breast cancer disease before surgery is undertaken.